Navigating Changes: Community Resettlement in Namibia Due to Nkurenkuru’s Urban Expansion - Annastasia Sinalumbu; Bruno Venditto (World)
This study critically investigates the socio-economic effects of urban expansion and forced relocation on peri-urban communities in Nkurenkuru, Namibia. Urban expansion in middle-income countries often has negative impacts on peri-urban and rural communities. Urban expansion leads to the displacement of such communities, and this study focuses on the socio-economic effects of such urbanization-induced displacement. This study used a qualitative research design, with in-depth interviews to chart the effects of relocation on community life and livelihoods. Findings reveal that before relocation, community members were involved in several land-use-related socio-economic activities. Relocation has worsened their living conditions with a significant drop in household income, financial stability, food security, and their access to vital services. Other findings include insufficient support from municipalities during the relocation process. This study shows the socio-economic repercussions of relocation and the importance of community consultations and participation in the urban expansion process.